Penerapan Metode Modeling untuk Mengoptimal Hasil Belajar Peserta Didik pada Materi Sholat Fardhu - Nur Zaini; Muhammad Nur Hadi (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2021)
The Modeling method has quite an important conceptual principle, because through Modeling students can avoid theoretical-abstract learning. The purpose of this study is to determine '' Application of Modeling Methods to Optimize Student Learning Outcomes in Fardhu Prayer Materials in Class 2 Mi Nurul Huda Patian Babat Lamongan. This research is a type of quantitative research with a correlational approach. The population in this study were students in grade 2 at Mi Nurul Huda Patian Babat, totaling 20 students. The sample in this study were all students in grade 2. The instruments used were questionnaires, documentation and observation, while testing the hypothesis using the product moment correlation formula. The results showed that the modeling method (X = 75%) was good and the students' morality (Y = 40%) was good, which was obtained by using the product moment correlation formula with significant results, namely (r count (0.602)> r table (0.444) ) that `` There is a correlation between modeling methods and student learning outcomes in the Fardhu prayer material in Class 2 Mi Nurul Huda Patian Babat Lamongan for the 2019-2020 academic year ''